Narrative inquiry invites professional development: educators claim the creative space of praxis - Latta, Margaret Macintyre; Kim, Jeong-Hee (My University, 2011)
The current educational context, particularly with the passage of the No Child Left Behind Act of 2001, calls for evidence-based measurable student learning outcomes. Increasingly, teachers feel that opportunities for their praxis are closed off to create, adapt, and discern within the act of teaching, leaving them with little felt agency in classrooms. In this paper, we explore how narrative inquiry used as a medium for professional development can create a needed space where teacher agency for praxis is fostered individually and collectively through understanding otherness. We conclude narrative inquiry invites participating educators to claim the creative space of praxis in their classrooms and fosters a culture of professional learning across participants that we see as the formative work necessary within professional development.
Keywords: Narrative inquiry; Praxis; Professional development; Creativity